Ageing medical workforce in Australia - where will the medical educators come from? - Callander Emily J; Fletcher Susan L; Schofield Deborah J (BMC, 2009)
Abstract Background As the general practitioner and specialist medical workforce ages there is likely to be a large number of retirees in the near future. However, few Australian studies have specifically examined medical practitioner retirement and projected retirement patterns, and the subsequent impact this may have on training future health care professionals. Methods Extracts from the Australian Medicare database and Medical Labour Force Surveys are used to examine trends in attrition of general medical practitioners and specialists over the age of 45 years from the workforce and to predict their rate of retirement to 2025. Results The general medical practitioner workforce has aged significantly (p < 0.05). Between the years 2000 and 2025, it was projected that 43% of the year 2000 general practitioner workforce and 56% of the specialist workforce would have retired. Conclusion The ageing of the baby boomer and older cohorts of the general practitioner and specialist workforce will lead to a significant number of retirements over the next 20 years. Increasing the numbers of students and new medical schools has been heralded as a means of alleviating service shortages from about 2015 onwards; however, the retirement of a large proportion of experienced health care professionals may lead to shortages of educators for these students.